2012
DOI: 10.1007/s10620-012-2323-0
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Effectiveness of Anti-TNF Agents for Crohn’s Disease in a Tertiary Referral IBD Practice

Abstract: After adjustment for prior anti-TNF there was no difference in remission rates between the IFX and ADA/CTZ groups at any time point post-baseline. This suggests that differences between groups were accounted for by a higher rate of prior anti-TNF in the ADA/CTZ group. Our results should be reviewed with caution given the small sample size.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
21
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(25 citation statements)
references
References 17 publications
4
21
0
Order By: Relevance
“…Infliximab, adalimumab, and certolizumab are all FDA-approved for CD, and infliximab, adalimumab, and golimumab are all approved for UC. Typical rates of clinical response and remission to these drugs in IBD appear similar in clinical trials and observational studies, in addition to secondary outcomes like hospitalizations and quality of life [3][4][5][6].…”
Section: Currently Available Biologic Agentsmentioning
confidence: 81%
“…Infliximab, adalimumab, and certolizumab are all FDA-approved for CD, and infliximab, adalimumab, and golimumab are all approved for UC. Typical rates of clinical response and remission to these drugs in IBD appear similar in clinical trials and observational studies, in addition to secondary outcomes like hospitalizations and quality of life [3][4][5][6].…”
Section: Currently Available Biologic Agentsmentioning
confidence: 81%
“…11,12 Retrospective and nonrandomised studies have demonstrated IFX and ADA to have similar clinical outcomes in avoidance of corticosteroids, surgery, hospitalisation and improvement in quality of life in patients with CD. [13][14][15][16][17] In summary, biologic and retrospective clinical data suggest similar therapeutic activity of these agents in CD. Head-to-head direct comparative efficacy trials among anti-TNF agents for CD have not been performed.…”
Section: Introductionmentioning
confidence: 88%
“…In such circumstances, anti-tumor necrosis factor therapy may be an alternative treatment for pyoderma gangrenosum. A previous comparison of the efficacy of infliximab and adalimumab for Crohn's disease in clinical practice showed no difference in the remission rates between the groups at any time point post-baseline (14). Hence, it follows that patients can select a therapeutic option based on its indications, the mode of administration, side effects, and the scientific evidence of its efficacy and safety.…”
Section: Discussionmentioning
confidence: 95%